2019
DOI: 10.4062/biomolther.2018.152
|View full text |Cite
|
Sign up to set email alerts
|

Possible Effects of Radiofrequency Electromagnetic Field Exposure on Central Nerve System

Abstract: Technological advances of mankind, through the development of electrical and communication technologies, have resulted in the exposure to artificial electromagnetic fields (EMF). Technological growth is expected to continue; as such, the amount of EMF exposure will continue to increase steadily. In particular, the use-time of smart phones, that have become a necessity for modern people, is steadily increasing. Social concerns and interest in the impact on the cranial nervous system are increased when consideri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
72
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(88 citation statements)
references
References 124 publications
(161 reference statements)
0
72
0
1
Order By: Relevance
“…It has been found that EMF can induce changes in nerve cells, the function of the nerve myelin, and ion channels; additionally, EMF can act as a stress source (33). There is a construction between EMF and neurodegenerative diseases such as headaches, seizures, nausea, and chronic pain (34).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that EMF can induce changes in nerve cells, the function of the nerve myelin, and ion channels; additionally, EMF can act as a stress source (33). There is a construction between EMF and neurodegenerative diseases such as headaches, seizures, nausea, and chronic pain (34).…”
Section: Discussionmentioning
confidence: 99%
“…To detect preamble positions, the received signal is multiplied with the known preamble signal via the convolution algorithm as Equation (1). The preamble positions in each image are the peak of the resulting signal as Figure 3.…”
Section: Match Filtermentioning
confidence: 99%
“…Various research groups worldwide have been investigating ways of improving upon the fifth-generation (5G) of digital cellular networks in the frequency band of millimeter waves that increase the data rate (1-10 Gbps). However, it is important to consider that RFs have potentially harmful effects on human health [1]. Therefore, researchers worldwide have attempted to find new technologies to replace RF technologies currently in use.…”
Section: Introductionmentioning
confidence: 99%
“…Some epidemiological studies have demonstrated that EMR may cause brain tumors [2,3], breast cancer [4], adrenal gland and heart tumors [5], etc. In addition, EMR may have adverse effects on the central nerve system [6] and the reproductive system [7,8] and give rise to stress and anxiety in behavior [9]. However, some other reports have given negative results, e.g., radiofrequency electromagnetic field (RF-EMF) could not give rise to cell apoptosis [10], global system communication (GSM) exposure did not significantly increase the apoptosis rate of neurons [11], mobile phone radiation did not induce pro-apoptosis effects in spermatozoa [12], 900 MHz electromagnetic fields (EMF) did not affect survival rates in female mice [13], and RF exposure did not affect the depression-like behavior, spatial memory, and brain histology in adolescent male mice [14].…”
Section: Introductionmentioning
confidence: 99%